Optical substrates for drug-metabolizing enzymes: Recent advances and future perspectives - Qiang Jin; JingJing Wu; Yue Wu; Hongxin Li; Moshe Finel; Dandan Wang; Guangbo Ge (Elsevier, 2022)
Drug-metabolizing enzymes (DMEs), a diverse group of enzymes responsible for the metabolic elimination of drugs and other xenobiotics, have been recognized as the critical determinants to drug safety and efficacy. Deciphering and understanding the key roles of individual DMEs in drug metabolism and toxicity, as well as characterizing the interactions of central DMEs with xenobiotics require reliable, practical and highly specific tools for sensing the activities of these enzymes in biological systems. In the last few decades, the scientists have developed a variety of optical substrates for sensing human DMEs, parts of them have been successfully used for studying target enzyme(s) in tissue preparations and living systems. Herein, molecular design principals and recent advances in the development and applications of optical substrates for human DMEs have been reviewed systematically. Furthermore, the challenges and future perspectives in this field are also highlighted. The presented information offers a group of practical approaches and imaging tools for sensing DMEs activities in complex biological systems, which strongly facilitates high-throughput screening the modulators of target DMEs and studies on drug/herb‒drug interactions, as well as promotes the fundamental researches for exploring the relevance of DMEs to human diseases and drug treatment outcomes.